Combination of different substrates to improve anaerobic digestion of sewage sludge in a wastewater treatment plant. (April 2016) - Park, Ki Young; Jang, Hyun Min; Park, Mee-Rye; Lee, Kwanyong; Kim, Daegi; Kim, Young Mo
Abstract: This study investigated the effects on methane production of combining diverse organic wastes as a method to improve the anaerobic digestion (AD) of sewage sludge in a wastewater treatment plant (WWTP). Evaluation of methane production from the AD of selected organic wastes showed the AD of food waste (FW) attained the highest methane production (522.9 mL CH4 /g VS), while the digestion of septage produced the lowest– (164.9 mL CH4 /g VS). Type of substrate determined the microbial community, possibly relating to differences in chemical properties of intermediates produced from the AD of wastes. Compared to the AD of primary sludge alone, co-digestion of primary sludge with FW achieved 72% higher methane production, while co-digestion with septage exhibited 20% lower production. Thus, the anaerobic co-digestion of sewage sludge with FW can provide a viable alternative to circumvent problems of separate digestion in WWTPs. Graphical abstract: Highlights: Digestibility of each substrate was tested for co-digestion with sewage sludge. Co-digestion of sewage sludge and food waste greatly enhanced methane yields. Food waste was proposed as a partner for co-substrate of sewage sludge.